Herramientas para instrumentación de programas paralelos en ambientes distribuidos - Tinetti, Fernando Gustavo (2006)
This paper presents a methodology and tool for instrumenting parallel programs in distributed computing platforms with the highest possible resolution (microseconds, if possible) and the minimum interference/overhead in programs. In the context of time instrumentation in distributed environments, it is essential to synchronize the involved clocks. In order to design the basic synchronizing algorithm, the classical strategies used in distributed environments were followed and adapted to the environment of a cluster or, at least, of an interconnection network to which there is exclusive (or controlled) access for the all communications carried out among the synchronized computers. This environment is specifically represented by those of parallel computing in clusters